(untitled) (Texas Journal of Engineering and Technology, 2023)
The main methods of approximation of magnetization curves are considered in the article. Requirements for approximating functions are given. Basic and approximated magnetization curves for various types of approximating functions were constructed and their deviation from experimental magnetization curves was determined. Conclusions on the choice of approximating functions and approximation methods are given.